UNLEASHING THE POWER OF VISUAL ENGAGEMENT: ANALYSIS OF VIDEO MARKETING STRATEGIES USED BY RESORTS IN LAIYA, BATANGAS - Charmaine P. Galano (Acta Informatica Malaysia)
This study explores the effectiveness of video marketing strategies used by resorts in Laiya, Batangas, focusing on enhancing brand recognition and customer conversion. It aims to determine the significant differences between factors influencing video marketing effectiveness and respondent profiles while exploring correlations between these factors and key success indicators of marketing campaigns. Various aspects influencing effectiveness, including social media platforms, video testimonials, influencer collaborations, and personalized videos, were analyzed through surveys and interviews. The study used a descriptive research design with a survey questionnaire. Data were gathered from 50 resort employees in San Juan, Batangas. Percentages, weighted mean, and correlation were the statistical treatments applied. Findings reveal perceptions and utilization patterns among respondents based on demographic characteristics and offer insights into audience preferences. Moreover, statistical analysis highlights critical relationships between effectiveness factors and success indicators, informing actionable recommendations for optimizing video marketing strategies. Finally, this research advises marketers and resort owners about leveraging visual engagement to strengthen brand visibility and customer engagement, fostering business growth in Laiya, Batangas.